Students' thought pattern concerning the greenhouse effect - Handayani, Rifati Dina; Prastowo, Sri Handono Budi; Prihandono, Trapsilo; Putra, Pramudya Dwi Aristya; Bachtiar, Rayendra Wahyu; Nuraini, Lailatul; Supriadi, Bambang; Maryani, Maryani; Bektiarso, Singgih; Lesmono, Albertus Djoko; Mahardika, I Ketut (Universitas PGRI Kanjuruhan Malang, 2021)
This study aims at investigating the Physics students' thought patterns concern-ing the greenhouse effect. Descriptive analysis was used, including the set of qualitative data. These data were then interpreted for their idea and content inductively to recognize students' thoughts and models concerning the greenhouse effect. The result confirmed three patterns of the students' thoughts concerning the greenhouse effect (patterns A, B, and C). The model covered different concepts, mechanisms, and processes of the greenhouse effect. The students' knowledge from science teacher explanations and books is not the only learning source concerning the educational environment. The issue and broadcast media frequently carry out confusing the concepts. This research is expected to provide physics teachers critical information to develop appropriate teaching methods and strategies concerning these topics.